Plasma Thiol redox status, cytokines and oxidative stress markers change in training activity of professional basketball players - Zembron-Lacny, A.; Slowinska-Lisowska, M. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The recent study showed that reactive oxygen species play a role in cell signaling through effects on thiol redox status. The change in thiol level stimulates or inhibits transcription factors activity, protein synthesis, cell growth and proliferation and inflammatory response (Valko et al. 2007). The aim of the paper was to evaluate the plasma concentration of inflammatory mediators including cytokines and their relation with thiol redox status and oxidative stress markers in training activity of basketball players. Methods: Sixteen males, professional players of the Polish Basketball Extraleague participated in this study. The plasma concentration of reduced glutathione (GSH), oxidized glutathione (GSSG), lipid peroxidation products (TBARS), protein carbonyls (PC), interleukine-6 (IL-6) and tumor necrosis factor a (TNFa) were measured in three successive training mezocycles (I high exercise load, II low exercise load, III high exercise load) during the preparatory period before the final, play-off round of the season. Thiol redox status was calculated according to the following equation: (GSH-2GSSG)/GSSG. Results: In the mezocycles II the exercise load was reduced whereas the levels of thiol redox status, TBARS, IL-6 and TNFa were increased compared with other mezocycles. The lowest level of tested parameters was observed in the mezocycles III. Thiol redox status correlated significantly with TBARS (r= 0.599), IL-6 (r= 0.390), TNFa (r= 0.461) and certainly with GSH (r= 0.716) and GSSG (r= -0.566). Oxidative stress markers did not correlate with cytokines levels. Conclusions: We conclude that professional training significantly affects thiol redox status and cytokines level as well as indicates direct relationship between thiol redox status and inflammatory response.